(untitled) (The Research of Medical Science Review, 2025)
Objective: To determine the outcome of children admitted with sepsis and to compare the in-hospital mortality in culture-negative sepsis (CNS) with culture-positive sepsis (CPS) patients. Methods: A total of 189 children with clinical diagnosis of sepsis with age 4-months to 16-years were recruited from 1-November-2024 to 31-January-2025. Venous blood samples were collected from all patients and sent to the hospital's microbiology department for analysis to determine whether they had CPS or CNS. Each patient was monitored through to their discharge from the hospital, with a maximum follow-up period of 30 days to assess in-hospital mortality rates. Results: The study involved 189 subjects with a mean age of 3.2±2.6 years. In terms of gender distribution, 103 (54.4%) of the participants were male. Regarding type of sepsis, CPS was diagnosed in 107 (56.6%) patients and CNS in 82 (43.3%) patients. Among the CPS group, 25 individuals (23.4%) experienced in-hospital mortality. In contrast, the CNS group, saw a lower mortality rate, with only 10 (12.2%) deaths (p-value 0.05). Conclusion: There is a significant number of pediatric patients having CNS admitted with sepsis suspicion. The mortality rate in CPS is higher in comparison to CNS patients.